(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Swedana, a revered therapeutic practice in Ayurveda, involves the induction of perspiration within the body. It serves as a crucial component in Ayurvedic treatments, serving as a modality which relieves Sheeta (coldness), Shoola (pain), Stambha (stiffness), Gaurava (heaviness), and confers Mruduta (softness) to the body. The aim of the study is to explore the action of Swedana through the Heat Shock Response (HSR). HSR is a cellular defense mechanism triggered by rise in temperature. Swedana therapy and its interplay with the Heat Shock Response is documented, shedding light on the scientific underpinnings of this traditional Ayurvedic practice.